Numerical Simulation Study of Steam Injection Optimization in Shallow Reservoir - Budi, Iwan; Oktaviani, Ajeng (Journal of Earth Energy Engineering, 2023)
In an EOR project, process improvement must be continually pursued since EOR is often marginally profitable. In steamflood EOR project, steam injection rate is very important parameter to ensure that each pattern reach maturity within a certain early period that result in high oil recovery and meet the economic hurdles. In particularly shallow formation settings, steam injection target is often difficult to achieve because limited by fracturing pressure to avoid breaching the cap rock and creating environmental problem. In this study we simulate steam injection in a typical heavy oil reservoir (high API, shallow depth, low pressure) to enable optimization of steam injection. A model has been built using typical shallow reservoir in using Builder-CMG. Wellan data, fluid model and operating conditions (injection strategy, steam quality) and expected/ forecasted performance. CMOST package is then used to design optimization study by varying the steam injection rate. The best scenario is based on the lowest reservoir pressure and cumulative SOR. We created three development options: regular inverted 7-spot 15.5-acre pattern, horizontal well and pattern size reduction (PSR). From this numerical study it is found that for the case studied, steam injection rate can be ramped up from 250 - 300 BSPD within 6-7 years, followed by peak production. A wind down injection rate to 0 can be used after this peak production to achieve CSOR target of 3-4 bbl of steam/bbl of oil. If a quicker SBT is required, then more steam injectivity is needed to put underground. Several scenarios can be considered as follow: (1) reducing the pattern size (thus adding steam via additional injection wells) and (2) utilizing horizontal wells.